The Concept of `Umūm al-Balwā in the Shade of Taṣawwuf: Wisdom Between Concession (Rukhsah) and Being Abstinence (Wara‘) - Abd Razak, Muhamad Afiq; Ramli, Mohd Anuar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
The teaching of Islam covers all aspects of a Muslim’s life. For Muslim, adherence towards Allah’s commandment is virtue. However, when it comes to difficult condition, Islam paved the way for easiness towards its adherents as the basic principle of divine revelation is meant to be no burden (raf‘ al-haraj). It is granted by Allah SWT, to provide easiness and concession when there are hardship and difficulty arise by a mukallaf in performing their devotion. One of the difficult condition in which mankind given exception is known as ‘umūm al-balwā (widespread hardship). This study is being carried out to view the concept of ‘umūm al-balwā within the taṣawwuf perspective in order to uncover the wisdom underlining them. To relate with taṣawwuf, ‘umūm al-balwā will be observed and compared with the concept of concession (rukhṣah) in fiqh and abstinence (wara‘) in taṣawwuf perspective. For this study, the issue of ‘umūm al-balwā in term of ḥalālan ṭayyiban food is being studied. This study utilized fully literature and textual analysis to gain the data as well as analysing the data. This study finds that the concept of ‘umūm al-balwā is relatable with taṣawwuf through the concept of warā‘. By understanding this relationship, it became a precious reflection for Muslim to practice their obedience and religious duties towards Allah better.